DESIGN AND DETERMINATION OF THE EFFICIENCY OF A SLANTING-TYPE SOLAR WATER DISTILLATION KIT (Nigerian Journal of Technology, 2017)
The solar water distillation system is a non-toxic and promising device for water purification. A slanting-type solar water distillation kit was fabricated and tested outdoor under the meteorological conditions of Imo State University, Owerri, Nigeria. The system consists of four major components; a wooden basin of surface area 0.16 m2, an absorber surface, a slanting glass roof and a condensate channel. Locally available materials were used to fabricate the solar still. The solar still produced an average of 0.09 m3 of distilled water per day, and this study was performed in the month of November, 2015. Daily efficiencies of the distillation kit were estimated and the average efficiency of the kit was found to be 7.7%. Though the efficiency is small as is peculiar to many solar systems, the output can be increased by increasing some parameters like the surface area, slanting angle of the roof, and the evaporation rate. Also, since the materials are readily available, one can fabricate as many solar distillation kits as possible to tackle the daily demand of potable water. Solar distillation kits can also serve as sources of distilled water for our hospitals and industries.http://dx.doi.org/10.4314/njt.v36i2.41